Addition of tungsten in Co/Al2O3 to catalyse the production of hydrogen through acetic acid steam reforming. Issue 10 (9th March 2023) - Wang, Yang; Li, Xinbao; Li, Pan; Zhu, Xinbo; Chen, Geng; Zhu, Yingying
Abstract: Steam reforming of bio‐oil is a promising green hydrogen production technology. Experimental and theoretical calculations have been carried out to study the performance of Co/Al2 O3 catalysts doped with tungsten (1–10 wt%) for bio‐oil model compound acetic acid steam reforming. The maximum acetic acid conversion of 95.4 % and H2 yield of 93.5 % were obtained over the 15Co‐5W/Al2 O3 catalyst under the optimized reaction conditions of temperature=550 °C, steam to carbon ratio=5 and the gas hourly space velocity of 15, 780 h −1 . The feeding capacity of the catalyst was improved by 2.3 times by the addition of 5 wt% W compared to that of the non‐W‐added Co/Al2 O3 catalyst. Catalyst characterizations by BET, XRD, H2 ‐TPR, XPS, HRTEM, and SEM were performed. The results showed that high activities were maintained over 20 h on the 15Co‐5W/Al2 O3 catalyst. A little filamentous coke was formed on the spent catalyst surface, and the agglomeration rate of active Co was relatively low. Density functional theory calculations confirmed that the adsorptions of CH3 COOH and H2 O on the catalyst were enhanced by the addition of W. Abstract : Acetic acid is a main component of biomass pyrolysis oil. A high yield of hydrogen is obtained through steam reforming of acetic acid over a tungsten‐modified Co/Al2 O3 catalyst. The interaction between the reactants and the catalyst surface is enhanced.